Towards “greening” trade? Tracking environmental provisions in the preferential trade agreements of emerging markets - Axel Berger; Clara Brandi; Dominique Bruhn; Manjiao Chi (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
With the adoption of the Sustainable Development Goals (SDGs) and the entry into force of the Paris Climate Agreement, the international community has inter alia pledged their commitment to economic development that is consistent with environmental sustainability. This paper focuses on the linkage between economic and environmental governance by tracking environmental provisions in preferential trade agreements (PTAs). While the United States and the European Union are frequently seen as innovators of “green” content in PTAs, systematic research on the role of emerging markets in promoting this development is scarce. For this reason, we develop an original, detailed dataset mapping the environmental content in 48 PTAs signed by the emerging markets China, India, Indonesia, Brazil and Mexico. Our findings clearly indicate a trend towards more environmental content in those countries' PTAs over time. At the same time, the data hint at patterns that suggest that these developments may at least be partly driven by Organisation for Economic Co-operation and Development (OECD) countries. The paper contributes to the literature on the design of PTAs, the linkage between trade and environment, as well as the role of emerging markets in global governance.
Keywords: 330; Handel und Investitionen; Umwelt; Ökosysteme und Ressourcen